Fabrication of TiO2 nanotubes and PDMS nanopillar by using anodization process to stamping technique. (2021) - Manisha,; Kumar, Vijay
Abstract: A great focus is pondered over the electrochemical anodization method, which offers a less intense synthesis process and results in uniform coverage of Titanium foil with titania nanotubes. After the different structural templates were prepared by different techniques, the surface morphology was done by Field Emission Scanning Electron Microscopy. Thereafter, the PDMS thin coating was done on the template by the spin coating method. To prepare a thick pattern of PDMS, the continuous layering of a dilute solution is done after drying it in an interval of time. After that, the sample was heated in an oven for a few hrs. to prepared molds. Then easily the PDMS mold was peeled off. titania template leaves an impression of the pore on the PDMS substrate and the nano impression of PDMS molds work as a top-electrode application.